2022
DOI: 10.1021/acsnano.2c00880
|View full text |Cite
|
Sign up to set email alerts
|

Facile and Scalable Synthesis of Whiskered Gold Nanosheets for Stretchable, Conductive, and Biocompatible Nanocomposites

Abstract: Noble metal nanomaterials have been studied as conductive fillers for stretchable, conductive, and biocompatible nanocomposites. However, their performance as conductive filler materials is far from ideal because of their high percolation threshold and low intrinsic conductivity. Moreover, the difficulty in large-scale production is another critical hurdle in their practical applications. Here we report a method for the facile and scalable synthesis of whiskered gold nanosheets (W-AuNSs) for stretchable, condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…Since W-AuNSs have whiskered morphology and nanometer range thickness 34 , they become highly interconnected but maintain a porous structure when they are dried from the dispersed solution state. As a result, the density of the dried W-AuNSs (i.e., W-AuNS network) is lower than the density of the dried forms of conventional metal nanomaterials such as silver nanowires (AgNWs) and gold nanosheets (AuNSs) (Extended Data Figs.…”
Section: Sequential Fabrication Methods Of Wau-cshsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since W-AuNSs have whiskered morphology and nanometer range thickness 34 , they become highly interconnected but maintain a porous structure when they are dried from the dispersed solution state. As a result, the density of the dried W-AuNSs (i.e., W-AuNS network) is lower than the density of the dried forms of conventional metal nanomaterials such as silver nanowires (AgNWs) and gold nanosheets (AuNSs) (Extended Data Figs.…”
Section: Sequential Fabrication Methods Of Wau-cshsmentioning
confidence: 99%
“…Preparation of metal nanomaterials W-AuNSs, AgNWs and AuNSs were synthesized by using the previously reported methods 26,34 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lim et al. [ 122 ] reported a facile and scalable synthesis approach to preparing whiskered Au nanosheets (W‐AuNS)‐based bioelectrode via in‐situ reaction, combined with the medical‐grade thermoplastic polyurethane (TPU) surface. After further modification with Pt, the W‐AuNS@Pt nanocomposites exhibited a large CSC c of 82 mC cm −2 and a significantly reduced impedance in the low‐frequency region.…”
Section: Materials Modification Strategies For Enhanced Neural Electr...mentioning
confidence: 99%
“…Moreover, the innovative mechanically tissue-like and highly conductive AuNPs embed elastomeric fiber electrodes demonstrated high SNRs of 3.1-4.2, and extremely reliable impedance over four months postimplantation (<20% variation) with reduced foreign body responses, thus encouraging a new paradigm of chronic recording and promoting better understanding the neural interfaces. Lim et al [122] reported a facile and scalable synthesis approach to preparing whiskered Au nanosheets (W-AuNS)-based bioelectrode via in-situ reaction, combined with the medical-grade thermoplastic polyurethane (TPU) surface. After further modification with Pt, the W-AuNS@Pt nanocomposites exhibited a large CSC c of 82 mC cm −2 and a significantly reduced impedance in the low-frequency region.…”
Section: Gold and Titanium Nitridementioning
confidence: 99%